If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 27 = x + 12 Reorder the terms: 27 + 4x = x + 12 Reorder the terms: 27 + 4x = 12 + x Solving 27 + 4x = 12 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 27 + 4x + -1x = 12 + x + -1x Combine like terms: 4x + -1x = 3x 27 + 3x = 12 + x + -1x Combine like terms: x + -1x = 0 27 + 3x = 12 + 0 27 + 3x = 12 Add '-27' to each side of the equation. 27 + -27 + 3x = 12 + -27 Combine like terms: 27 + -27 = 0 0 + 3x = 12 + -27 3x = 12 + -27 Combine like terms: 12 + -27 = -15 3x = -15 Divide each side by '3'. x = -5 Simplifying x = -5
| 5(2x-2)=3(4-2x) | | -2-5n=-5n^2 | | 3x+9/15=6 | | 8x^2+8xy-20y=0 | | -x+9=1/3(-9x+6)+1 | | -3(3r+3)=5-7r | | 5x-1-4x=x+17 | | 16-7*2= | | N^2+6=5N | | -3n+9+8n=7n-8n-9 | | 12x+2=4x-22 | | n+7/4=7/20 | | 5x=5/8 | | (4y-1)+(2x+5)=180 | | 6n-2=6n-7 | | 6w^2+24w-72=0 | | A^2-3A-3=5 | | 2x-16-x=x-16 | | 5x^2+24=0 | | 3y^2+51y+90=0 | | 3x=24*0.5 | | 3x+9/15=16 | | 8-9x=80 | | -x^2=36 | | -6x-10=-4x-14 | | 2x-21-x=x-21 | | 3xx-1=x+4 | | -9x-8=x-48 | | 37=5-x+3x | | -4/3t=-16 | | 3x?-1=x+4 | | 5y^2-45y+70=0 |